Biomarkers of muscle and cartilage damage and inflammation during a 200 km run - Kim, H. J.; Lee, Y. H.; Kim, C. K. (European Journal of Applied Physiology, 2007)
Ultra-marathon running is frequently associated with muscle fibre damage. However, ultra-marathon related information is scarce. The present study evaluated muscle and cartilage biomarkers, and cytokine secretion during a 200 km running event. Venous blood samples from 54 trained male ultra-marathon runners (mean ± SD, 45.7 ± 5.1 years). Plasma creatine phosphokinase (CPK), lactate dehydrogenase (LDH), aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate, glucose, high-sensitivity C-reactive protein (Hs-CRP), interleukin-6 (IL-6), TNF-? and serum cartilage oligomeric matrix protein (COMP) content were determined before, midway and immediately after the race. CPK increased 90-fold (19-fold at 100 km) from pre-race value and LDH increased 3.7-fold (2.2-fold at 100 km). AST increased 15-fold (5-fold at 100 km) and ALT increased 3.9-fold (2-fold at 100 km). Blood lactate and glucose levels did not change significantly. Hs-CRP increased 23-fold (3-fold at 100 km) and IL-6 increased 121-fold at 100 km, and then remained stable up to 200 km, whereas TNF-? did not change significantly. Serum COMP increased 3-fold (1.3-fold at 100 km). Post-run CPK was correlated with LDH (r = 0.62, P < 0.001), Hs-CRP (r = 0.45, P < 0.001), ALT (r = 0.89, P < 0.001), AST (r = 0.97, P < 0.001), and IL-6 (r = 0.61, P < 0.001). The present study demonstrated that blood biomarkers related to muscle and cartilage damage and inflammation were increased during a 200 km run and that this was particularly marked during the second half of the event. Ultra-marathon running clearly has a major impact on muscle and cartilage structures.